Olga Spence many changes - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1970)
Olga (Kennedy?) Spence describes life in Port au Choix past and present. She recounts a visit with Wilfred Grenfell. Speaks about telegraph operators. Rufus Guinchard (1899-1990) is shown fiddling. Producer /director George Billard. Archive: Val Earle